Supporting college students’ understanding of integral by using maple-integrated workbook - Lestiana, Herani Tri; Oktaviani, Dian Nataria (Department of Mathematics, Universitas Negeri Semarang, 2019)
A factor that contributes to students’ low performance in Calculus is that some teachers and lecturers tend to explain the concept of integral by using a set of symbols, notations, and rules without providing any contexts or representations of the concept. This study was aimed at supporting college students’ understanding of integral by integrating Maple in the learning process using Maple-integrated workbook. This study adapted Brog and Galls’ procedures which consist of collecting preliminary information, planning, developing, validation and preliminary revision, field test, and final revision. The subject of this study was college students’ of Mathematics Education Department of UPS Tegal. The result showed that module developed was in a good criteria, and the conceptual understanding test showed that 82,4% students in the experimental class got a score of 71 or higher. Moreover, the average score of the experiment and control class also confirmed that the average of students’ score in experiment class was significantly higher than that of students in control class.